In Search of Indigenous Educational Sovereignty - Forsythe, Laura (2018)
Completing a comprehensive survey of the education clauses in forty-one self-governance agreements between different First Nations and the Canadian government regarding educational sovereignty demonstrates that these agreements are not delivering First Nations educational sovereignty. The agreements do not provide First Nations with the autonomy and freedom needed to develop a curriculum framework outside of the provincial or territorial standard. Analyzing the exact clauses and how their wording expands or limits First Nations’ ability to govern educational content and implementation provides an opportunity to identify methods to address these issues in future negotiations. This research provides an opportunity to begin to answer the call for action by the Assembly of First Nations to review all existing documents and make recommendations for their continuance, revision, and termination and to influence the ninety agreements currently under negotiation in Canada. October 2018